1996
DOI: 10.1002/(sici)1098-1063(1996)6:6<601::aid-hipo5>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

A theory of hippocampal function in memory

Abstract: First, what is computed by the hippocampus is considered. Based on the effects of damage to the hippocampus and neuronal activity recorded in the primate hippocampus, it is suggested that it is involved in associating together information usually originating from different cortical regions, for example, about objects and their place in a spatial environment. The rapid formation of such context-dependent memories i s prototypical of memories of particular events or episodes. Second, a computational theory of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
313
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 444 publications
(343 citation statements)
references
References 82 publications
25
313
0
5
Order By: Relevance
“…The results showed that rats with DG lesions spent significantly less time exploring the two objects that were displaced relative to controls, indicating that DG lesions impair the detection of metric distance changes. Rats with CA3 or CA1 lesions displayed mild impairments relative to controls, providing empirical validation for the role of DG in spatial pattern separation and support the predictions of computational models (Rolls, 1996;Rolls & Kesner, 2006). Stark, Yassa, and Stark (2010) used an analogous task to that used for rats (Goodrich-Hunsaker et al, 2005) to measure spatial pattern separation based on distance, and in this case angle as well, to test young and healthy aging humans.…”
Section: Pattern Separation --Spatial Attributesupporting
confidence: 52%
See 1 more Smart Citation
“…The results showed that rats with DG lesions spent significantly less time exploring the two objects that were displaced relative to controls, indicating that DG lesions impair the detection of metric distance changes. Rats with CA3 or CA1 lesions displayed mild impairments relative to controls, providing empirical validation for the role of DG in spatial pattern separation and support the predictions of computational models (Rolls, 1996;Rolls & Kesner, 2006). Stark, Yassa, and Stark (2010) used an analogous task to that used for rats (Goodrich-Hunsaker et al, 2005) to measure spatial pattern separation based on distance, and in this case angle as well, to test young and healthy aging humans.…”
Section: Pattern Separation --Spatial Attributesupporting
confidence: 52%
“…This process is akin to the idea that the hippocampus is involved in orthogonalization of sensory input information (Rolls, 1989), in representational differentiation (Myers, Gluck, & Granger, 1995), and indirectly in the utilization of relationships (Cohen & Eichenbaum, 1993). Rolls' (1996) model proposes that pattern separation is facilitated by sparse connections in the mossy-fiber system, which connects DG granular cells to CA3 pyramidal neurons. Separation of patterns is accomplished based on the low probability that any two CA3 neurons will receive mossy fiber input synapses from a similar subset of DG cells.…”
Section: Pattern Separation --Spatial Attributementioning
confidence: 99%
“…Detailed explanations of hippocampal roles in both spatial and non-spatial tasks are available [72,173,196,225]. The theories themselves have converged on a basic hippocampal functionality in which hippocampal cellular activity follows from an interaction of external cue representations, internal dead-reckoning (path-integration) representations, and contextual representations, all processed through an intrinsic autoassociator system within the hippocampus [76,108,171,173,177,185].…”
Section: Resultsmentioning
confidence: 99%
“…By activation, we mean that the hippocampus proper and especially CA3 becomes an environment-specific autoassociative network (Lisman 1999; Rolls 1996; Mizumori et al 1989). This network is environment specific because discharge is confined to an environment-specific subset of the pyramidal cells—those that are place cells in the environment.…”
Section: Discussionmentioning
confidence: 99%